A novel ANFIS model to prediction of the density of n-alkane in different operational condition. (17th December 2019) - Rajabi Kuyakhi, Hossein; Tahmasbi Boldaji, Ramin
Abstract: The density has an important role in the oil and gas industries calculation. In this study, an adaptive neuro-fuzzy interference system (ANFIS) model was employed to predict the density of n-alkane. The result obtained by the ANFIS model analyzed with the statistical parameters (i.e., MSE, RMSE, and R 2 ) and graphical method. According to the result obtained the ANFIS has the highest accuracy with R 2 = 0.999, MSE = 0.1438, and RMSE = 0.3792.